2014
DOI: 10.2527/jas.2014-7530
|View full text |Cite
|
Sign up to set email alerts
|

Pressure load on specific body areas of gestating sows lying on rubber mats with different softness1

Abstract: Rubber mats offer a possibility to increase lying comfort for sows with positive effects on sow lying behavior and health. However, until now, no information has been reported about the relationship between the softness of rubber mats and the pressure load on certain body areas of sows. We used a total of 68 (40 multiparous, 28 primiparous) German Landrace × German Landrace sows with a BW within the range of 90 to 330 kg (divided in 3 weight classes) to measure peak force and distribution of pressure during ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At the beginning of the study, the prevalence of lameness was similar within treatments: 23% ([ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]) in treatment RM vs. 21% ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]) in treatment C ( p = 0.33). No Treatment*Cycle interaction ( p < 0.05) was observed for any of the parameters under study, suggesting that the effect of rubber mat was constant over the two observed gestation periods.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…At the beginning of the study, the prevalence of lameness was similar within treatments: 23% ([ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]) in treatment RM vs. 21% ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]) in treatment C ( p = 0.33). No Treatment*Cycle interaction ( p < 0.05) was observed for any of the parameters under study, suggesting that the effect of rubber mat was constant over the two observed gestation periods.…”
Section: Resultsmentioning
confidence: 96%
“…These farms previously encountered lameness issues in sows. The prevalence of lameness in the three farms was 22% (confidence interval of 95% [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]) at the beginning of the study. Two of them (Farms A and B) had 250 sows and the third (Farm C) had 700 sows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation